2007
DOI: 10.1111/j.1365-294x.2007.03261.x
|View full text |Cite
|
Sign up to set email alerts
|

Subterranean archipelago in the Australian arid zone: mitochondrial DNA phylogeography of amphipods from central Western Australia

Abstract: In 1998, a unique subterranean ecosystem was discovered in numerous isolated calcrete (carbonate) aquifers in the arid Yilgarn region of Western Australia. Previous morphological and genetic analyses of a subterranean water beetle fauna suggest that calcrete aquifers are equivalent to closed island habitats that have been isolated for millions of years. We tested this hypothesis further by phylogeographic analyses of subterranean amphipods (Crangonyctoidea: Paramelitidae and Hyalidae) using mitochondrial DNA s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
86
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(95 citation statements)
references
References 44 publications
8
86
0
1
Order By: Relevance
“…data). These findings have been observed in other crustaceans, particularly amphipods and parabathynellids (Cooper et al 2007Guzik et al 2008; K. M. Abrams, unpubl. data).…”
Section: Methodology For Estimating Subterranean Faunal Diversitymentioning
confidence: 88%
See 3 more Smart Citations
“…data). These findings have been observed in other crustaceans, particularly amphipods and parabathynellids (Cooper et al 2007Guzik et al 2008; K. M. Abrams, unpubl. data).…”
Section: Methodology For Estimating Subterranean Faunal Diversitymentioning
confidence: 88%
“…Using DNA alone~90 new crustacean 'lineages' were identified from published studies (e.g. up to 21 Pilbara amphipods (Finston and Johnson 2004;Finston et al 2007Finston et al , 2009, 22 Yilgarn amphipods (Cooper et al 2007), 1 anchialine shrimp (Page et al 2008), 24 aquatic isopods ) and 17 parabathynellids (Guzik et al 2008)). Each of these studies also demonstrated geographic isolation for each of the lineages (as above) confirming our species concept using a combined approach as exemplified by Harvey et al (2008) where both morphological and molecular data reinforced conclusions.…”
Section: Methodology For Estimating Subterranean Faunal Diversitymentioning
confidence: 99%
See 2 more Smart Citations
“…This functional approach to the provision of groundwater ecosystem services complements current studies of stygofaunal systematics and phylogenetics (e.g. Cooper et al 2002Cooper et al , 2007Watts and Humphreys 2006), revealing how groundwater ecosystem services may vary with changes in assemblage composition over time, the likely effects of species loss or invasion, and potential influences of aquifer habitat fragmentation. Such insights can guide protection and restoration of aquifers and their ecosystem services as well as contributing to one of the most exciting fundamental ecological questions of our time.…”
Section: Introductionmentioning
confidence: 93%